An Integrated Flow–Electric–Thermal Model for a Cylindrical Li‐Ion Battery Module with a Direct Liquid Cooling Strategy. Issue 8 (6th July 2022) - Yin, Litao; Geng, Zeyang; Björneklett, Are; Söderlund, Elisabeth; Thiringer, Torbjörn; Brandell, Daniel
Abstract : An integrated model is constructed for a Li‐ion battery module composed of cylindrical cells by coupling individual first‐order equivalent circuit models (ECMs) with a 3D heat transfer model, also considering the fluid flow dynamics of the applied cooling liquid, and bench‐marked against experimental data. This model simulates a representative unit of the battery module with direct liquid cooling in a parallel configuration. Instead of assigning specific values to the featured parameters involved in the ECMs, they are here defined as 4D arrays. This makes it possible to simultaneously consider the effect of the state of charge, current rate, and temperature on the battery dynamics, making the model more adaptive, versatile, and connectable to the battery cell electrochemistry. According to the simulation results, the model employing state‐dependent battery properties fits better with the experimental cooling results. Additionally, the temperature uniformity of the module with a parallel cooling configuration is improved compared to a serial configuration. However, the increase of the absolute core temperature cannot be directly controlled by the surface cooling due to the slow heat transport rate across the battery material. The simulations also provide directions for the modification of module design, to the potential benefit of battery pack developers. Abstract : An integrated flow–electric–thermal model for cylindrical Li‐ion battery modules is established, which couples individual equivalent circuit models (ECMs) with a 3D heat transfer model, and takes the flow dynamics of the coolant into account. The featured parameters involved in the ECMs are defined as a series of 4D arrays, which provides a better fitting between simulation and experimental cooling test results.